Electroless deposition and characterization of Fe/FeOx nanoparticles on porous carbon microspheres: structure and surface reactivity - Colavita, Paula (My University, 2013)
There has been great interest in synthetic methods that yield supported iron and iron oxide nanoparticles in order to prevent aggregation and improve their transport properties, handling and surface reactivity. In this work we report on the use of electroless deposition methods for the synthesis of carbon-supported iron/iron-oxide (Fe/FeOx) nanoparticles. We have used carbon porous microspheres synthesized via ultraspray pyrolysis as carbon scaffolds for the nucleation and growth of iron nanoparticles. The reported electroless deposition approach results in composite Fe/FeOx/carbon microspheres of narrowly dispersed size. A combination of X-ray powder diffraction (XRD) and X-ray absorption spectroscopies (EXAFS and XANES) was used in order to determine the structure and composition of the Fe/FeOx/carbon microspheres. Microspheres were found to display (14 ± 1)% iron content (w/w), whereby (12 ± 3)% of iron atoms were present as metallic iron and the remaining as maghemite (Fe2O3). Finally, we show that the removal capacity of Fe/FeOx/carbon microspheres for Cr(VI) is (20 ± 2) mg g−1 and that the maximum surface density for Cr adsorbates is (60 ± 6) μg m−2, thus suggesting that these are promising materials for the removal of water pollutants from aqueous solution.
PUBLISHED
Keywords: Synthetic methods; Iron-oxide; Iron nanoparticles